2019
DOI: 10.1016/j.bbmt.2018.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Extended CCR5 Blockade for Graft-versus-Host Disease Prophylaxis Improves Outcomes of Reduced-Intensity Unrelated Donor Hematopoietic Cell Transplantation: A Phase II Clinical Trial

Abstract: Graft-versus-host disease (GVHD) remains the most common treatment-related complication after allogeneic hematopoietic cell transplantation (allo-HCT). Lymphocyte migration plays a critical role in the pathogenesis of GVHD. A previous phase I/II trial demonstrated that CCR5 blockade with maraviroc in the first 30 days after allo-HCT resulted in a low incidence of early acute GVHD, primarily in visceral organs, but with no impact on late acute or chronic GVHD. We conducted a phase II trial to examine the effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…As with the CSH model, we found that the time-dependent AUC of the selected model was higher that the AUC from a model containing only the maraviroc treatment variable, but confidence intervals overlapped; at , the selected model’s AUC was 0.78 (0.43–1.0) versus 0.60 (0.36–0.80); and at , 0.84 (0.58–1.0) versus 0.72 (0.56–0.84). We also found that patients treated with maraviroc were less likely to experience aGVHD24 than controls, consistent with previous studies 41 . We estimated a SHR of 0.25 (0.08–0.78), considering relapse and cGVHD as competing risks; the earlier point estimate of 0.42 was derived with only death as a competing risk 27 .…”
Section: Resultssupporting
confidence: 92%
“…As with the CSH model, we found that the time-dependent AUC of the selected model was higher that the AUC from a model containing only the maraviroc treatment variable, but confidence intervals overlapped; at , the selected model’s AUC was 0.78 (0.43–1.0) versus 0.60 (0.36–0.80); and at , 0.84 (0.58–1.0) versus 0.72 (0.56–0.84). We also found that patients treated with maraviroc were less likely to experience aGVHD24 than controls, consistent with previous studies 41 . We estimated a SHR of 0.25 (0.08–0.78), considering relapse and cGVHD as competing risks; the earlier point estimate of 0.42 was derived with only death as a competing risk 27 .…”
Section: Resultssupporting
confidence: 92%
“…Short-term addition of CCR5 antagonist, maraviroc added to standard GVHD prophylaxis resulted in reduced GI and liver GVHD in allo-HSCT patients given reduced intensity conditioning ( 72 ). Compared to this short-term treatment of 1 month ( 72 ), the extended course of maraviroc (3 months) was also safe and resulted in a significantly improved survival and higher GVHD-free ( 73 ). The relationship between conditioning regimen intensity and efficacy of CCR5 antagonism in allo-HSCT patients is unknown and warrants investigation.…”
Section: Blocking T Cell Chemokine Receptor Directed Migration Into Gmentioning
confidence: 99%
“…Two phase I/II trials have now tested the safety and the efficacy of CCR5 blockade using maraviroc for the prevention of aGvHD. The first trial, conducted in adults [197], proved successful and led to follow-up studies by the same group of researchers [198,199,200,201,202] as well as an ongoing phase II study (NCT01785810). Another trial [203], published in 2019, included adults and children but had inconclusive findings due to unrelated toxicities.…”
Section: Resultsmentioning
confidence: 99%